(untitled) (LEARNing Landscapes, 2014)
Inclusive education in Alberta is entangled in a long, dark history of exclusion. Hermeneutics can help illuminate and interrupt this entanglement in order to ask what might be taken for granted within it. Our notions of inclusion could be interpreted as suffering from an inability to recognize what is still historically at play, especially in the case of students diagnosed with emotional and behavioural disabilities. Seeing and understanding this through a hermeneutic sense of historical inquiry and play can help us move towards socially just school systems for children and youth.